Towards a uniformitarian account of creole similarity: Gender loss in Martinican Creole - Térosier, Stéphane (Proceedings of the Linguistic Society of America, 2025)
This paper argues that it is possible to develop a uniformitarian account of at least some of the similarities. With the adoption of the Interpretability Hypothesis (Hawkins & Hattori 2006; Tsimpli & Dimitrakopoulou 2007), it is predicted that uninterpretable features are particularly vulnerable and may be lost in creole genesis because of the critical role of L2 acquisition in this process. In contrast, inter-pretable features are more resilient. Thus, it is predicted that, under the assumption of a feature interpretability-based analysis of gender (Kramer 2014, 2015), grammatical gender is very likely to be lost during creolization, while natural gender is more likely to be retained. These predictions are shown to be borne out in Martinican Creole. Because the Interpretability Hypothesis does not rely on the assumption of an impoverished input, the study suggests that there is no need to postulate that creoles develop out of pidgin to account for some of their similarities. It is, therefore, a welcome result of the study that it suggests a way to improve the predictive power of a uniformitarian approach to creole formation.